On Production Smoothing - Klein, Morton (Management Science, 1961)
The production planning model of Modigliani and Hohn and the smoothing model of Hoffman and Jacobs are combined. The most interesting result is that the horizon planning properties of the individual models are retained in the combined model. Methods are also given for the computation of optimal production schedules for certain kinds of requirements schedules.